Understanding the physiology of Lactobacillus plantarum at zero growth - Philippe Goffin; Bert van de Bunt; Marco Giovane; Johan H J Leveau; Sachie Höppener‐Ogawa; Bas Teusink; Jeroen Hugenholtz (Molecular Systems Biology)
Abstract Situations of extremely low substrate availability, resulting in slow growth, are common in natural environments. To mimic these conditions, Lactobacillus plantarum was grown in a carbon‐limited retentostat with complete biomass retention. The physiology of extremely slow‐growing L. plantarum—as studied by genome‐scale modeling and transcriptomics—was fundamentally different from that of stationary‐phase cells. Stress resistance mechanisms were not massively induced during transition to extremely slow growth. The energy‐generating metabolism was remarkably stable and remained largely based on the conversion of glucose to lactate. The combination of metabolic and transcriptomic analyses revealed behaviors involved in interactions with the environment, more particularly with plants: production of plant hormones or precursors thereof, and preparedness for the utilization of plant‐derived substrates. Accordingly, the production of compounds interfering with plant root development was demonstrated in slow‐growing L. plantarum. Thus, conditions of slow growth and limited substrate availability seem to trigger a plant environment‐like response, even in the absence of plant‐derived material, suggesting that this might constitute an intrinsic behavior in L. plantarum.